Pandangan Hukum Islam terhadap Ketentuan Hilangnya Kekuatan Hukum Surat Wasiat pada Pandemi Covid-19 - M. Agustia Maradika Wildan; Inayatul Anisah (Rechtenstudent, 2022)
A will is a form of gift whose implementation is carried out when the giver of the will dies. The implementation of a will can be done using oral or written methods. The purpose of a will is to make it known to other people, but in the Civil Code there is a rule that a will made during a pandemic suddenly becomes invalid, although in practice this rule does not apply to Muslims in Indonesia. The focus of the problems studied are: 1) What are the provisions for the loss of legal force in a will made during the Covid-19 pandemic based on the Civil Code Article 950 Paragraph 1?; 2) How does Islamic Law regulate the loss of legal force in a will made during the Covid-19 pandemic based on the Civil Code Article 950 Paragraph 1? This study uses a qualitative approach with a normative juridical type of research which aims to obtain views of Islamic Law regarding provisions regarding the loss of legal force in wills made during the Covid-19 pandemic in the Civil Code. The results of the research are that the validity period of a will made during the Covid-19 pandemic based on Article 950 Paragraph 1 of the Civil Code is 6 (six) months and if it exceeds that time, it loses its legal force. Meanwhile, the view of Islamic law is that a will remains legally enforceable as long as the will is not revoked by the testator.